William H. Bridges (Editor), Digest of the Charters and Ordinances of the City of Memphis, from 1826 to 1867, Inclusive, Together with the Acts of the Legislature Relating to the City, with an Appendix, 50 (1867), § 4864 - (:unkn) unknown (My University, 1867)
Prohibited selling, loaning, or giving to a minor a pistol, Bowie knife, dirk, Arkansas tooth-pick, hunter's knife, or like dangerous weapon, except a gun for hunting or self defense in traveling. Punishable by fine of minimum $25 and imprisonment.
Keywords: TRANSFER - MINORS